1999
DOI: 10.1097/00126334-199907010-00010
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of Injection Drug Users to Participate in an HIV Vaccine Efficacy Trial in Bangkok, Thailand

Abstract: We assessed willingness to participate in an HIV recombinant gp120 bivalent subtypes B/E candidate vaccine efficacy trial among 193 injection drug users (IDUs) attending drug treatment clinics in Bangkok, Thailand. IDUs previously enrolled in a prospective cohort study were invited to group sessions describing a potential trial, then completed questionnaires assessing comprehension and willingness to participate. A week later, they completed a follow-up questionnaire that again assessed comprehension and willi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 13 publications
3
37
0
Order By: Relevance
“…However, the protective effect of any available HIV candidate vaccines is still uncertain; the high response rates in both groups may reflect insufficient information in relation to the experimental characteristics of the hypothetical vaccine. Like in other Asian studies [21], social relationship and fear of the exclusion of community were found to be independent predictors for WTP in our study sample. It is suggested that efforts should be made to increase awareness of the importance and reduce the stigma of participating in HIV vaccine trials among both high-risk groups, who are potential vaccine trial participants, and general population whose attitudes may affect participants' decision.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, the protective effect of any available HIV candidate vaccines is still uncertain; the high response rates in both groups may reflect insufficient information in relation to the experimental characteristics of the hypothetical vaccine. Like in other Asian studies [21], social relationship and fear of the exclusion of community were found to be independent predictors for WTP in our study sample. It is suggested that efforts should be made to increase awareness of the importance and reduce the stigma of participating in HIV vaccine trials among both high-risk groups, who are potential vaccine trial participants, and general population whose attitudes may affect participants' decision.…”
Section: Discussionsupporting
confidence: 85%
“…This percentage is higher than other studies among IDUs in both Asian and western countries [21][22]. Besides IDUs, men who have sex with men (MSM) and women at heterosexual risk have also been most involved in HIV vaccine trials.…”
Section: Discussionmentioning
confidence: 82%
“…This indicates a need to develop strategies and materials for those in secondary or vocational school and ensuring that all presentations are well adapted to the target audience. Such recommendations had been made in similar studies [16]. The level of willingness to participate found in the present investigation was slightly higher than that which have been found in a similar study in the Northern part of Nigeria and Uganda [7,17].…”
Section: Discussionsupporting
confidence: 57%
“…Knowledge and attitude toward HIV vaccines are among the factors that may influence participation in trials and the eventual acceptability of efficacious vaccines. [10][11][12][13][14][15] We found a significant difference in the level of knowledge before and after vaccine education in our study sample. However, only 63% of the participants understood that initial HIV vaccines are expected to be only partially efficacious.…”
Section: Discussionmentioning
confidence: 47%
“…Previous studies suggest that sociodemographic characteristics and risk behavior are associated with WTP. 10,11,[13][14][15]22 According to a report from a WHO-UNAIDS consultation, 23 WTP in trials varies depending on educational level, perception of risk, and age. Altruism and a desire for protection are common motivations for participation and vaccine safety is usually the major concern.…”
Section: Discussionmentioning
confidence: 99%